Nondispersive Raman lines in the D‐band region for ferrocene functionalized carbon nanotubes. Issue 12 (8th October 2014) - Kuzmany, H.; Shi, L.; Pichler, T.; Kramberger, C.; Chernov, A.; Liu, X.
<x xml:space="preserve">Abstract</x> Carbon‐rich fillers like ferrocene can be transformed into an inner tube with extremely small diameter if they are filled into HiPco tubes. For ferrocene@HiPco three new Raman bands appear in the D‐band region during this transformation. These bands do not show dispersion and exhibit a strong resonance for red laser excitation. The observed resonance is for the outgoing phonon at 1247 cm<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2jcbg30d" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />−1</alternatives> for an electronic transition at 1.84 eV. Maximum response for the new lines is observed for transformation of the filled tubes between 800 and 900°C. In addition to the three bands in the D‐band region also an enhanced band at 470 cm<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2jcbg2qg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />−1</alternatives> is observed with the same sensitivity to transformation temperature. In order to obtain more information on the origin of the new bands deuterium substituted FeCp<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2jcbg2t4" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2</alternatives> was used. The new lines turned out to be sensitive to this substitution which is considered as a strong indication of their origin from organic compounds created inside or in between the tubes during the transformation process.